Novel lipidized analogs of prolactin-releasing peptide have prolonged half-lives and exert anti-obesity effects after peripheral administration - Maletínská, L; Nagelová, V; Tichá, A; Zemenová, J; Pirník, Z; Holubová, M; Špolcová, A; Mikulášková, B; Blechová, M; Sýkora, D; Lacinová, Z; Haluzík, M; et al. (International journal of obesity (2005), 2015)
OBJECTIVES: Obesity is a frequent metabolic disorder but an effective therapy is still scarce. Anorexigenic neuropeptides produced and acting in the brain have the potential to decrease food intake and ameliorate obesity but are ineffective after peripheral application. We have designed lipidized analogs of prolactin-releasing peptide (PrRP), which is involved in energy balance regulation as demonstrated by obesity phenotypes of both PrRP- and PrRP-receptor-knockout mice. RESULTS: Lipidized PrRP analogs showed binding affinity and signaling in PrRP receptor-expressing cells similar to natural PrRP. Moreover, these analogs showed high binding affinity also to anorexigenic neuropeptide FF-2 receptor. Peripheral administration of myristoylated and palmitoylated PrRP analogs to fasted mice induced strong and long-lasting anorexigenic effects and neuronal activation in the brain areas involved in food intake regulation. Two-week-long subcutaneous administration of palmitoylated PrRP31 and myristoylated PrRP20 lowered food intake, body weight and improved metabolic parameters, and attenuated lipogenesis in mice with diet-induced obesity. CONCLUSIONS: Our data suggest that the lipidization of PrRP enhances stability and mediates its effect in central nervous system. Strong anorexigenic and body-weight-reducing effects make lipidized PrRP an attractive candidate for anti-obesity treatment.
Keywords: energetický metabolismus; Male; Half-Life; Obesity; regulace chuti k jídlu; přijímání potravy; signální transdukce; obezita; mužské pohlaví; Eating; Signal Transduction; Prolactin-Releasing Hormone; látky proti obezitě; lipidy; Animals; Energy Metabolism; Appetite Regulation; zvířata; myši inbrední C57BL; Anti-Obesity Agents; myši; hormon uvolňující prolaktin; Mice, Inbred C57BL; Lipids; Mice; poločas